Sensor, Signal, and Imaging Informatics in 2017 - Hsu, William; Deserno, Thomas M; Kahn, Charles E., Jr; Section Editors for the IMIA Yearbook Section on Sensor, Signal and Imaging Informatics (Yearbook of Medical Informatics, 2018)
Objective: To summarize significant contributions to sensor, signal, and imaging informatics literature published in 2017.Methods: PubMed® and Web of Science® were searched to identify the scientific publications published in 2017 that addressed sensors, signals, and imaging in medical informatics. Fifteen papers were selected by consensus as candidate best papers. Each candidate article was reviewed by section editors and at least two other external reviewers. The final selection of the four best papers was conducted by the editorial board of the International Medical Informatics Association (IMIA) Yearbook.Results: The selected papers of 2017 demonstrate the important scientific advances in management and analysis of sensor, signal, and imaging information.Conclusion: The growth of signal and imaging data and the increasing power of machine learning techniques have engendered new opportunities for research in medical informatics. This synopsis highlights cutting-edge contributions to the science of Sensor, Signal, and Imaging Informatics.
Keywords: Signal processing; biomedical imaging; deep learning; radiomics